Maqashid Sharia Review Of Decisions Shar'iyah Idi Court In Divorce Cases - Lukmanul Hakim (Rechtsnormen: Journal of Law, 2023)
Background.  Divorce is a matter that is never finished to be studied and discussed. Even cases of divorce cases continue to increase. One of them is the divorce case. Purpose. Many divorce cases are contested due to the background between husband and wife not wanting to carry out their obligations, such as providing a living physically and spiritually, but when analyzed this is not the main thing that causes divorce but rather bad communication between husband and wife, in deciding a divorce case a judge are required to be thorough and observant in deciding on a divorce so that a legal basis and fair considerations are needed so that a positive decision is born for both parties. Method. In this study, the authors used qualitative legal research and normative legal research, namely what we know as library law research, namely legal articles conducted by researching based on materials sourced from the literature. Results. Research results: 1) The factor in the occurrence of divorce is due to not fulfilling a living, harming/endangering the wife, one party leaves the other party without permission and without a valid reason, one party gets a prison sentence of 5 years or more after the marriage takes place, Jidal or syiqaq (prolonged and unresolved quarrels), infidelity or one party commits adultery, one party commits violence/nusuz, apostasy or converts. 2) Every decision made by the Panel of Judges of the Syari'yah Idi Court remains based on legal aspects and Maqasid Syari'ah, both ahwal asyahksiyah cases in general and divorce cases in particular, as the purpose of law is to protect the rights of each individual both from the perspective of Life, religion, reason, property, lineage and honor. Conclusion. As an answer to the formulation of the problem and the results of the author's analysis, it can be concluded that: The factor in the occurrence of divorce is due to the absence of a living.